Binge Watching and the Role of Social Media Virality towards promoting Netflix's Squid Game. (July 2022) - Ahmed, Wasim; Fenton, Alex; Hardey, Mariann; Das, Ronnie
The management literature has extensively studied viral marketing in the last decade; however, there is a lack of research in understanding network structures and the role of influencers within popular cultural consumption, such as on-demand digital media and binge-watching. In this article, we investigate the role of social media in popularising the East Asian dystopian cultural drama Squid Game. We studied this phenomenon by analysing social network structures, dynamics and influencer characteristics that transformed Squid Game into a popular global digital cultural consumption sensation. Stemming from the foundational theories of popular culture binge-watching, network theory and the social media echo chamber effect, we demonstrate how careful 'seeding' and 'broadcasting' behaviour adopted by Netflix and key influencers helped the 'reciprocal merging' of creative media content within the broader social media space. Our study found that 13, 727 Twitter users were tweeting or mentioned on the day show was released. Our research findings further present the characteristic of individual group-based echo chambers and their role in value co-creation towards expanding the network boundary through e-WOM. This phenomenon led to the show's unprecedented popularity amongst a global audience within a short period. Contributions of our work expand viral marketing and echo-chamber concepts into the binge-watching and popular digital culture realm, where the interplay between dramatized Asian and Western dystopian social norms provided the very fabric of user-led promotion and value co-creation.